Avaliação de cenários de sistemas de energia nuclear utilizando modelos MESSAGE - Fidéllis Bitencourt Gonzaga Louzada e Estanislau (2019)
The growth of energy demand, especially in the electric sector, international policies to mitigate the effects of climate change and the worldwide trend of decarbonisation of the economy put nuclear energy as an important option for the energy mix of the countries. Its importance, as a base energy, bringing safety and reliability to the energy sector, requires studies to evaluate growth projections and their impacts. Nuclear power accounted for 2.5 percent of Brazil's electricity supply in 2017. Brazil, with one of the world's largest reserves of uranium, also dominates the nuclear fuel cycle, although it does not have the installed capacity to supply all demand of its nuclear power plants. At the national level, the search for independence of the nuclear energy sector is discussed. Thus this work aims to evaluate scenarios with projections of the national expansion of nuclear energy. In this context, this paper reviews some externalities in nuclear energy and evaluates, through the MESSAGE modeling tool, the generation history and other five scenarios operating in nuclear open fuel cycle and closed fuel cycle. Both fuel cycles are compared and results measure greenhouse gas emissions, the utilization of national reserve resources, the capacities required during the fuel cycle stages for the independence of the sector, the waste generated to be managed and the economic aspects, such as fuel cycle expenses and plant operation and maintenance costs. Mainly, it is concluded that in the scenarios of less expansion of nuclear generation, the small participation in the electrical matrix requires strategic definitions that guarantee the reliability and safety of the system. Also, scenarios operating in closed cycle have lower requirements during the fuel cycle, as well as lower GHG emissions and less waste to be managed despite the small increase in the cost of electricity.